2020
DOI: 10.3389/fvets.2020.00494
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Allometry: Anatomy, Movement, and Foraging Behavior of Three Cattle Breeds of Different Productivity

Abstract: Pauler et al. Grazing Allometry of Cattle Breeds composition influenced cattle behavior: On pastures of low forage quality, animals walked more, foraged more selectively, and used space less evenly. In conclusion, the observed breed-specific differences can be used to improve pasture management and grassland conservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 65 publications
4
31
1
Order By: Relevance
“…However, these differences in grazing selection were minimal compared to those expressed within breeds on pastures with different botanical composition or under different grazing management (21,27), as was also observed in the present study, when forage of different vegetation growth stage was offered in June and July. Still, the breed differences in grazing selection were lower than expected and were in contrast to the results of Farruggia et al (35), who showed that lactating cattle with high nutrient requirements grazed more selectively than dry cows, and Pauler et al (22,23), who found that more productive Angus × Holstein cattle grazed more selectively than Highland cattle. However, Dumont et al (36) also did not find relevant differences in grazing behavior among traditional and specialized breeds.…”
Section: Discussion Differences Among Breeds In Grazing Selectioncontrasting
confidence: 63%
See 1 more Smart Citation
“…However, these differences in grazing selection were minimal compared to those expressed within breeds on pastures with different botanical composition or under different grazing management (21,27), as was also observed in the present study, when forage of different vegetation growth stage was offered in June and July. Still, the breed differences in grazing selection were lower than expected and were in contrast to the results of Farruggia et al (35), who showed that lactating cattle with high nutrient requirements grazed more selectively than dry cows, and Pauler et al (22,23), who found that more productive Angus × Holstein cattle grazed more selectively than Highland cattle. However, Dumont et al (36) also did not find relevant differences in grazing behavior among traditional and specialized breeds.…”
Section: Discussion Differences Among Breeds In Grazing Selectioncontrasting
confidence: 63%
“…Dairy cattle grazing on biodiverse pastures express preference or aversion for some specific plants that can vary according to their nutrient requirements and experience. Therefore, the actual diet ingested by the animals might differ from the average vegetation available on the pasture (20,21), and this according to individual or breed-specific behavior (22,23). Consequently, FA and terpene composition of the milk might vary among animals grazing the same biodiverse grassland.…”
Section: Introductionmentioning
confidence: 99%
“…The Scottish Highland cattle, which overlap with the park cattle, are a rare breed known for low beef productivity and are mainly used in land management [69,70]. Described as being 'less affected by breeding' they have thrived in open, harsh environments [71] and are able to survive in marginal landscapes [72].…”
Section: (B) Behavioural Selectionmentioning
confidence: 99%
“…Livestock breeds influence the functioning of the agroecosystems [55], as breeds differ in numerous functional traits, including their feeding preferences, metabolism, behavior, etc. [56]. Thus, they channel energy fluxes between trophic levels and participate in nutrient cycles [57,58].…”
Section: Livestock Breeds As Mediators Of Ecosystem Servicesmentioning
confidence: 99%
“…Some literature seems to point toward minor significance of livestock breeds on grazing [65][66][67]. However, more recent studies have shown the effects of livestock breeds on pasture vegetation composition and plant traits [68][69][70], related to body size, foraging behavior, movements, and specific body traits [56,68]. Other examples are resistance to diseases, greenhouse gas emissions, or habitat provision.…”
Section: Livestock Breeds As Mediators Of Ecosystem Servicesmentioning
confidence: 99%